Green Insights of Textile Industry in Bangladesh: A Case Study on Mozart Knitting Ltd. - Aktar , Mst. Afroja (Global Disclosure of Economics and Business, 2014)
The effectiveness of individual units of an Effluent Treatment Plant (ETP) agrees on the entire performance of the plant and the ultimately echoing effluent standard. In this study, an ETP of a composite textile industry in Bangladesh was investigated using this method. After completion of the stipulated study, findings came into force illustrated that water samples had been collected from the dyeing unit and accordingly had been used for the ETP and also been determined for the key parameters. The results were used to identify problems with the treatment units and broadly suggested for modifications. Simple but fully-bodied methodology was developed for assessing the performance of various treatment units and the ETP as a whole that could be implemented by ETP managers on a regular basis for improving the performance so that the effluent meets national standard as well as conforms to the requirements of international standard which is a compliance of the international buyers. To comply with the BB Guidelines commercial banks have taken initiatives on financing to the textile dyeing units in question with the implementation of ETP.  The ETP’s performance on Mozart Knitting Ltd. shown that it has been performing with the underprivileged management, especially chemical dosing were affecting the ETP’s performance and that simple measures could address the problems. A number of equipment i.e middle pathways rolling, water transferring pipes should repair without more ado.JEL Classification Code: L67, K32